In vitro and in vivo correlates of physiological and neoplastic human Fallopian tube stem cells. Issue 4 (9th January 2016) - Yamamoto, Yusuke; Ning, Gang; Howitt, Brooke E; Mehra, Karishma; Wu, Lingyan; Wang, Xia; Hong, Yue; Kern, Florian; Wei, Tay Seok; Zhang, Ting; Nagarajan, Niranjan; Basuli, Debargha; et al.
Abstract: High‐grade serous cancer (HGSC) progresses to advanced stages without symptoms and the 5‐year survival rate is a dismal 30%. Recent studies of ovaries and Fallopian tubes in patients with BRCA1 or BRCA2 mutations have documented a pre‐metastatic intramucosal neoplasm that is found almost exclusively in the Fallopian tube, termed 'serous tubal intraepithelial carcinoma' or STIC. Moreover, other proliferations, termed p53 signatures, secretory cell outgrowths (SCOUTs), and lower‐grade serous tubal intraepithelial neoplasms (STINs) fall short of STIC but share similar alterations in expression, in keeping with an underpinning of genomic disturbances involved in, or occurring in parallel with, serous carcinogenesis. To gain insight into the cellular origins of this unique tubal pathway to high‐grade serous cancer, we cloned and both immortalized and transformed Fallopian tube stem cells (FTSCs). We demonstrated that pedigrees of FTSCs were capable of multipotent differentiation and that the tumours derived from transformed FTSCs shared the histological and molecular features of HGSC. We also demonstrated that altered expression of some biomarkers seen in transformed FTSCs and HGSCs (stathmin, EZH2, CXCR4, CXCL12, and FOXM1) could be seen as well in immortalized cells and their in vivo counterparts SCOUTs and STINs. Thus, a whole‐genome transcriptome analysis comparing FTSCs, immortalized FTSCs, and transformed FTSCs showed a clear molecular progression sequence that is recapitulated by the spectrum of accumulated perturbations characterizing the range of proliferations seen in vivo . Biomarkers unique to STIC relative to normal tubal epithelium provide a basis for novel detection approaches to early HGSC, but must be viewed critically given their potential expression in lesser proliferations. Perturbations shared by both immortalized and transformed FTSCs may provide unique early targets for prevention strategies. Central to these efforts has been the ability to clone and perpetuate multipotent FTSCs. Copyright © 2015 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.